Effects of Affectively-Loaded Childhood-Related Photos From the IAPS on the Induction of Involuntary Autobiographical Memories in Young and Older Adults - Navarro, Beatriz; Jimeno, Verónica; Fernández-Aguilar, Luz; Nieto, Marta; Toledano González, Abel; Cantero, María José; Ros, Laura; Latorre, José Miguel (Frontiers, 2024)
Objective: Aging produces changes in emotional reactivity and the retrieval of autobiographical memories. The main aim of this study was to assess age-related differences, comparing emotion induction and autobiographical memory recall using photos from the International Affective Picture System (IAPS) that are thematically related to childhood. Method: A cross-sectional observational study was conducted, with the participation of 327 individuals (168 young adults and 159 older adults) with no cognitive impairment and aged between 18 and 88 years. We showed the participants a set of five pictures from the IAPS, the affective content of which was related to childhood. Two of these were considered to be positive images, two negative and one neutral, according to the valence of these pictures in the literature. The main study variables were the reactions associated with emotional valence or pleasure, arousal and dominance, after viewing the photos, and the autobiographical memories retrieved by the participants. Results: The younger adults retrieved a larger number of memories than their older counterparts. As regards the responses to the five affective pictures (IAPS) on valence, arousal and dominance (IAPS), statistically significant differences were only found for pictures 2,345 (BlackEye), with a more positive valence in the group of older adults and higher arousal in the young ones, and 2,312 (Mother), with a more positive valence in the group of older persons. A greater number of memories were retrieved for the photos that generated higher levels of pleasure, greater relaxation and greater emotional control. Conclusion: Of the variables that may be associated with the elicitation of involuntary autobiographical memories, the most significant are age and a positive stimulus.
Keywords: Autobiografía; Fotografía - Aspectos emocionales; Trastornos cognitivos; Photos; Autobiographical memories; Young adults; Older adults; Cognitive impairment